A Comparative View of Terrorist Acts and Legislative Measures Countering this Phenomenon in Albania and the United States of America - Lirime Çukaj (Academicus International Scientific Journal, 2013)

(untitled)
Terrorist acts have been a worrisome phenomenon for all nations. Paradoxically, although states have been conscious about the danger of this phenomenon, there is no definition of terrorist acts so far. States have been skeptical and they have not agreed that the judgment of these criminal offences be performed by international jurisdictions, thus opting for the domestic jurisdiction. Nevertheless, states have lacked the willingness to establish joint criminal policies and find efficacious means to combat these terrorist acts. One of these efficacious means has been the seizure and confiscation of licit and illicit assets possessed by terrorist groups. This is the focus of this short study, which will be inclusive by viewing this topic under the general framework of international acts, our domestic legislation, as well as the American one. This paper aims at presenting the legislative measures taken by the Albanian state to meet international requirements. It endeavors to provide arguments why all licit and illicit assets associated with terrorist acts are seized and confiscated. Special attention is paid to the way these assets are administered. Moreover, this study tries to analyze the achievements and problems in Albania, as well as provide conclusions and recommendations.